2019
DOI: 10.1002/jac5.1092
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists' perceptions of implementing a pharmacist‐managed area under the concentration time curve‐guided vancomycin dosing program at a large academic medical center

Abstract: Introduction A pharmacist‐managed area‐under the concentration time curve/minimum inhibitory concentration (AUC/MIC)‐based vancomycin dosing and monitoring strategy was implemented at the University of Maryland Medical Center (UMMC) in January 2017. Because this was a large change in practice and methodology, we sought to understand pharmacists' perceptions of the practice before and after implementation. Methods A mixed methods preimplementation survey was sent to all pharmacists, including residents, complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Limited work has been undertaken to understand user integration of TDM interventions into routine workflow [ 8 , 15 , 16 ]. This study applied the TDF to synthesise barriers and facilitators to user uptake of a pilot TDM Service.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited work has been undertaken to understand user integration of TDM interventions into routine workflow [ 8 , 15 , 16 ]. This study applied the TDF to synthesise barriers and facilitators to user uptake of a pilot TDM Service.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have explored factors influencing uptake of TDM interventions have identified barriers including poor coordination of TDM processes, time constraints, perceived lack of user competency and the prescribing hierarchy [ 8 , 15 , 16 ]. While these findings are useful, systematically identifying barriers and facilitators to uptake using a theory-based framework provides an evidence-based approach to enhance intervention design and achieve successful integration into routine workflow [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…8 Another pharmacist-only vancomycin AUC transition survey also found an overall increased perception of patient safety. 9 Based on the idea that efficacy is unlikely to be impacted regardless of TDM method due to achieving AUC ≥ 400 mg*h/L in most cases with trough concentrations >15 mg/L, it is not surprising that the respondents in our postintervention survey believed that the change would not lead to increased efficacy. 10 In fact, likely due in part to our education efforts, most of the postintervention survey respondents chose "no difference" in efficacy, whereas in the preintervention survey, 57.3% thought an increase in efficacy would be achieved.…”
Section: Discussionmentioning
confidence: 94%